PEMBEKALAN ILMU DIGITAL MARKETING UNTUK MENINGKATKAN PENJUALAN KERUPUK BERAS PANTI ASUHAN ACHMAD YANI KOTA PONTIANAK - Azazi, Anwar; Alaydrus, Hafidz Rifqi; Ariandini, Aulia; Agustin, Dela; Pratama, Agung Hidayat; Bosrin, Adrian (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2024)
The Ahmad Yani Orphanage in Pontianak City faces challenges in marketing its rice cracker product due to limited knowledge of digital marketing. This community service aims to provide digital marketing knowledge to increase the orphanage's product sales. The method used includes lectures, discussions, and direct practice over one month with 16 participants. Activities encompass digital marketing training, Canva workshops, video content creation, new product development, and handicraft making. The results show improved participant understanding of digital marketing, ability to create promotional content, and new product development. The orphanage now has a more effective digital marketing strategy, attractive promotional content, and a new product (amplang) to market.